2008
DOI: 10.1016/j.physletb.2008.04.060
|View full text |Cite
|
Sign up to set email alerts
|

Growth index of DGP model and current growth rate data

Abstract: Recently, some efforts focus on differentiating dark energy and modified gravity with the growth function δ(z). In the literature, it is useful to parameterize the growth rate f ≡ d ln δ/d ln a = Ω γ m with the growth index γ. In this note, we consider the general DGP model with any Ω k . We confront the growth index of DGP model with currently available growth rate data and find that the DGP model is still consistent with it. This implies that more and better growth rate data are required to distinguish betwe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
94
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 73 publications
(97 citation statements)
references
References 85 publications
3
94
0
Order By: Relevance
“…[27,28]. Recently, the use of the growth rate of matter perturbation in addition to the expansion history of the Universe to differentiate dark energy models and modified gravity attracted much attention [29,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44].…”
Section: (1 + 2ωmentioning
confidence: 99%
“…[27,28]. Recently, the use of the growth rate of matter perturbation in addition to the expansion history of the Universe to differentiate dark energy models and modified gravity attracted much attention [29,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44].…”
Section: (1 + 2ωmentioning
confidence: 99%
“…Specifically, the idea of utilizing the so-called growth index, γ (first introduced by [16]), of linear matter perturbations as a gravity tool is not new and indeed there is a lot of work in the literature. There are plenty of studies available in which one can find the theoretical form of the growth index for various cosmological models, including scalar field DE [17][18][19][20][21][22], DGP [21,[23][24][25], Finsler-Randers [26] and f (R) [27,28].…”
Section: Introductionmentioning
confidence: 99%
“…In the case of the concordance ΛCDM model (w(z) = −1) the above formula reduces to γ ≈ 6/11. Considering the braneworld model of [18] we have γ ≈ 11/16 (see [12,19,20,21]). Finally, for some f (R) gravity models it has been found that γ ≃ 0.415 − 0.21z for various parameter values (see [22,23]), while for the Finsler-Randers cosmology, Basilakos & Stavrinos [24] found γ ≈ 9/14.…”
Section: Introductionmentioning
confidence: 99%